1976
DOI: 10.1136/jcp.29.1.42
|View full text |Cite
|
Sign up to set email alerts
|

EB virus antibody and infectious mononucleosis in a boarding school for boys.

Abstract: sYNoPsis A study of EB virus antibody was undertaken in a boarding school for boys between 11 and 18 years of age; 35 % of boys had EBV antibody when first sampled and a small number acquired antibody each year. Some of these boys had had no recorded illness during the period before the first positive sample and some developed classic infectious mononucleosis which was accompanied by a positive heterophil antibody test and detection of EB virus specific IgM. In a school of 800 boys there were 13 cases of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The following sera weie examined: 1 serial sera, including pre-illness and post-convalescent sera, from 61 cases of IM from the university study partially reported in 1971 (University Health Physicians and Public Health Laboratory Service Laboratories, 1971); 2 serial sera from healthy students known to have IgG antibody for EB virus; 140 at university and 55 at a boarding school for boys (Hoskins et al, 1976); 3 1469 single sera sent to the Cross-Infection Refer-1036 ence Laboratory at Colindale for anti-streptolysin 0 (ASO) antibody estimation, representing patients of all ages; 4 63 sera from untreated cases of Hodgkin's disease, kindly supplied by Professor Peckham and Dr. B. Jameson from the Royal Marsden Hospital; 5 22 sera from babies less than 6 weeks old who were found to have maternal EBV IgG.…”
Section: Methodsmentioning
confidence: 99%
“…The following sera weie examined: 1 serial sera, including pre-illness and post-convalescent sera, from 61 cases of IM from the university study partially reported in 1971 (University Health Physicians and Public Health Laboratory Service Laboratories, 1971); 2 serial sera from healthy students known to have IgG antibody for EB virus; 140 at university and 55 at a boarding school for boys (Hoskins et al, 1976); 3 1469 single sera sent to the Cross-Infection Refer-1036 ence Laboratory at Colindale for anti-streptolysin 0 (ASO) antibody estimation, representing patients of all ages; 4 63 sera from untreated cases of Hodgkin's disease, kindly supplied by Professor Peckham and Dr. B. Jameson from the Royal Marsden Hospital; 5 22 sera from babies less than 6 weeks old who were found to have maternal EBV IgG.…”
Section: Methodsmentioning
confidence: 99%